Digitization of Learning Through Virtual Laboratory in Assessing Students' Science Process Skills on Mechanical Wave Material - Prihatiningtyas, Suci; Haryono, Heny Ekawati; Putra, Ino Angga (Universitas Pendidikan Mandalika, 2024)
This study explores the impact of utilizing the PhET virtual laboratory on the development of science process skills among students. Conducted with a repeated treatment design (one group pretest-posttest design), the research involved 30 eleventh-grade science students from MA Bahrul Ulum Jombang. Throughout the study, students engaged with mechanical wave topics using the PhET virtual simulations. Their science process skills were meticulously evaluated through various scientific approaches including problem formulation, hypothesis development, identification of variables, data interpretation, and the ability to draw logical conclusions. The results revealed a marked improvement in these skills following the intervention with the virtual laboratory. Specifically, students demonstrated enhanced abilities in forming coherent hypotheses, accurately identifying relevant variables, and effectively interpreting complex data sets. Moreover, their skills in synthesizing information to formulate valid conclusions were significantly bolstered. The use of the PhET virtual laboratory not only fostered a deeper understanding of mechanical wave concepts but also facilitated a more interactive and engaging learning environment. These findings advocate for the broader integration of such technological tools in science education, emphasizing their role in enriching students' learning experiences and advancing their analytical and scientific thinking skills.